In-Service Efficiency Estimation with the use Modified Air-Gap Torque Method for Squirrel-Cage Induction Motor - Figura, R.; Szychta, E.; Szychta, L. (Elektronika ir Elektrotechnika, 2011)
Energy-efficient industrial drives and control systems are designed to minimize power consumption. Energy consumption is associated with the efficiency of energy conversion in electric motors. In the paper the nonintrusive efficiency estimation method for induction cage motor was shown. The implementation of the method was based on the air-gap torque method. The results were compared with those obtained with the classical air-gap torque method. The authors present a significant impact of estimation of mechanical power losses in the engine on the accuracy of estimating the coefficient of efficiency cage induction motor. Ill. 7, bibl. 24, tabl. 3 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.114.8.696